ANALISIS PERBEDAAN PROSES PEMBENTUKAN POS UPAYA KESEHATAN KERJA (UKK) DI KOTA SEMARANG - Husnan Khair, Muhammad Dyas; Sriatmi, Ayun; Kurniawan, Bina (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Pos UKK is series of occupational health efforts organized from, by and for the working community in the informal sector. From the 6 units of Pos UKK in Semarang City only 2 units are included in the active category. Before Pos UKK operates, there are processes of forming Pos UKK which must be implemented in order to function properly so it need further research on how is the forming processes between active and inactive Pos UKK. This research aims to analyze the differences in the processes of forming Pos UKK in Semarang City. This research uses quantitative method with cross sectional approach. The population in this research are 53 people from active Pos UKK and 93 people from inactive Pos UKK and the amount of samples were 35 people from each criteria of Pos UKK. Data analysis include univariate analysis with presentation of frequency distribution table and bivariate analysis using Mann-Whitney test. The results of univariate analysis show that practice, attitude, knowledge, belief, motivation, accessibility, co-worker support, owner support, and Puskesmas support on respondents from active Pos UKK tend to be better than respondents from inactive Pos UKK. The results of bivariate analysis show that there were significant differences in practice, attitude, knowledge, accessibility, co-worker support, owner support and Puskesmas support. While there were no significant difference of belief and motivation. It is recommeded to the Puskesmas to conduct the initial survey to improve self assessment ability, provide incentives with money, re-socialize and conduct Pos UKK revitalitation. Dinas Kesehatan is also advised to make procedures for the implementation of a more operational Pos UKK formation processes and to hold competition between Pos UKK.